KERJASAMA TAIWAN DAN SINGAPURA DALAM AGREEMENT BETWEEN SINGAPORE AND THE SEPARATE CUSTOMS TERRITORY OF TAIWAN, PENGHU, KINMEN AND MATSU ON ECONOMIC PARTNERSHIP (ASTEP) - Sikumbang, Edwin Janara; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The ratification of Agreement between Singapore and The Separate Customs Territory of Taiwan, Penghu, Kinmen and Matsu on Economic Partnership (ASTEP) is worth to be examined. In one hand, Republic of China in Taiwan since its establishment has difficult situations in the international affairs by the fact that it doesn’t have political status as a country by de jure and by the One China Policy provided by Mainland China gives pressures to countries which have intention to make relationship with Taiwan. In the other hand, Singapore is a country that holding the One China Policy, since it have diplomatic relations to People’s Republic of China, and currently doesn’t have any formal diplomatic relation with Taiwan.This research has structured with the perspective of Neo-liberalism and supported with Cooperation Theory and then applied the concept of Interdependency. Formulation of all arguments, facts, and theoretical framework are guided by qualitative explanation methods. Scope of this research is Taiwan economic strategies within ASTEP along Singapore which is considered as nation-state in the methodology of International Relations.The Researcher has presented the result in this paper which explain why Taiwan making a bilateral trade agreement with Singapore and how Taiwan using its status and name as the Separate Customs Territory of Taiwan, Penghu, Kinmen and Matsu instead of its official name Republic of China. This research has revealed the strategy of Taiwan to get involved in Asia Pacific Region’s trade affairs, and establish more of free trade agreements with other countries in Asia Pacific.Kata kunci: Free Trade Agreement, Bilateral Economic Partnership, Republic of China, Taiwan, Singapore, ASTEP, Asia Pacific.